Formal features for a syntactic-semantic classification of predicative adjectives in Brazilian Portuguese - Martinez, Ryan Marçal Saldanha Magaña; Vale, Oto Araújo (Anais do Simpósio Brasileiro de Tecnologia da Informação e da Linguagem Humana (STIL); 2023: Anais do XIV Simpósio Brasileiro de Tecnologia da Informação e da Linguagem Humana, 2023)
Syntactic-semantic classification of words relies ultimately on the selection of appropriate formal features. This is a bibliographic study discussing the applicability and relevance to Brazilian Portuguese of features proposed to correlate to semantics in large-scale work on predicative adjectives. These include distributional features of subjects, complements, prepositions, and copular verbs, as well as transformational features (i.e., those obtained by information-preserving rephrasing of sentences). The results of this bibliographic search suggest that 40 of the formal properties registered in other work are promising for dividing Brazilian Portuguese adjectives into syntactic-semantic classes.